Peran PT. Pertamina Patra Niaga Integrated Terminal Surabaya Sebagai Upaya Masyarakat Penyelamatan Sumber Daya Air Bagi Masyarakat Dalam Program CSR Geblak Jambangan - Beti Nur Hayati; Nuril Khatulistiyawati; Ita Puspitasari; Buyung Satria Permana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
The condition of decreasing water quality also occurs in the Brantas River. This pollution is mostly caused by domestic waste caused by the lack of public awareness in disposing of waste in its place. Based on these problems PT. Pertamina (Persero) Integrated Terminal Surabaya, as one of the corporate entities that stands around the location provides a program that aims to deal with this problem through the Jambangan Right Behind Movement (Geblak) program. The research method used in this paper is descriptive qualitative. The result of this research is PT. Pertamina (Persero) Integrated Terminal Surabaya has a role as a facilitator and catalyst. There are several stages that have been passed since the beginning of the program, namely assessment, engagement, action and facilitation. The impact can be seen in changes in environmental conditions that used to be slums to become organized, as well as reducing waste that is converted into goods of economic value.